Effect of electron beam irradiation on natural rubber/linear low density polyethylene blends with m-phenylenebismaleimide - Nor Hayati Muhammad,; Ibrahim Abdullah,; Dahlan Hj. Mohd, (Universiti Kebangsaan Malaysia, 2011)
The effects of HVA-2 on radiation-induced cross-linkings in 60/40 natural rubber/ linear low density polyethylene (NR/LLDPE) blends was studied. NR/LLDPE was irradiated by using a 3.0 MeV electron beam machine with doses ranging from 0 to 250 kGy. Results showed that under the irradiation employed, the blends NR/LLDPE were cross-linked by the electron beam irradiation. The presence of HVA-2 in the blends caused the optimum dose to decrease and the blends to exhibit higher tensile properties. Further, within the dose range studied, the degradation caused by electron beam irradiation was found to be minimal. The optimized processing conditions were 120oC, 50 rpm rotor speed and 13 min processing time. The gel content, tensile strength, elongation at break, hardness and impact test studies were used to follow the irradiation-induced cross-linkings in the blend. For blends of 60/40 NR/LLDPE with 2.0 phr HVA-2, the optimum tensile strength and dose, were 19 MPa and 100 kGy, respectively. Blends of 60/40 NR/LLDPE without HVA-2, the optimum tensile strength and dose were 17.2 MPa and 200 kGy, respectively.